Complications in Pregnancy and Foetal Outcomes in Gestational Diabetes – An Observational Study in a Tertiary Hospital in Nigeria (Academia Journal of Medicine, 2018)
Background: A retrospective cohort study to compare the pregnancy complications and foetal outcomes in pregnancies complicated by  diabetes mellitus. Subjects and Methods: One hundred and eighty five diabetic pregnant patients who delivered at the Department of  Obstetric & Gynecology, University of Nigeria, Nsukka. during the 3-year-period formed the subjects of this study. There were 27(14.6%)  (type 1) - insulin dependent diabetics, group 1, 19 (10.2%)(type 2), non insulin dependent diabetic patients who constituted group 2 and  139(75.2 %) gestational diabetic patients who made up group 3. Data extracted from the case files included maternal age, gravidity, parity ,  number of abortions, gestational age at booking, time of diagnosis of diabetes mellitus, complications during pregnancy, birth weight, placental  weight. Results: There were no statistically significant differences in the three groups regarding the mean gravidity, parity, birth weight and  placental weight (p>0.05). However, statistically significant differences were found with respect to the mean maternal age, gestation at  booking, fasting blood sugar, and gestation at delivery (p
Keywords: Pregnancy; Gestational diabetes; Antenatal complications; Foetal outcomes.